2020
DOI: 10.1089/pop.2019.0093
|View full text |Cite
|
Sign up to set email alerts
|

Seeking Consensus on the Terminology of Value-Based Transformation Through use of a Delphi Process

Abstract: Collaboration among diverse stakeholders involved in the value transformation of health care requires consistent use of terminology. The objective of this study was to reach consensus definitions for the terms value-based care, value-based payment, and population health. A modified Delphi process was conducted from February 2017 to July 2017. An in-person panel meeting was followed by 3 rounds of surveys. Panelists anonymously rated individual components of definitions and full definitions on a 9-point Likert … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The exclusion criteria for all yielded studies were “not a peer-reviewed paper and/or journal,” “no empirical data,” “not part of/contributing to VBHC or synonym,” “no relation to the healthcare professional,” “only about VBHC education,” “only about value-based payment or synonym,” and “non-English.” In absence of consensus on a VBHC definition ( 4 ), we relied on the authors' judgement i.e., any study in which the original author identified the intervention as “value-based healthcare” or its synonyms was assumed to be about VBHC. We identified a healthcare professional as anyone caring for, or aiming to cure, patients or clients with a formal training to do so.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The exclusion criteria for all yielded studies were “not a peer-reviewed paper and/or journal,” “no empirical data,” “not part of/contributing to VBHC or synonym,” “no relation to the healthcare professional,” “only about VBHC education,” “only about value-based payment or synonym,” and “non-English.” In absence of consensus on a VBHC definition ( 4 ), we relied on the authors' judgement i.e., any study in which the original author identified the intervention as “value-based healthcare” or its synonyms was assumed to be about VBHC. We identified a healthcare professional as anyone caring for, or aiming to cure, patients or clients with a formal training to do so.…”
Section: Methodsmentioning
confidence: 99%
“…Healthcare systems increasingly move toward “value-based healthcare” (VBHC) ( 1 ), aiming to further improve quality and performance of care as well as the equitable, sustainable, and transparent use of resources ( 1 – 3 ). Thus far, a globally shared definition of VBHC is lacking ( 4 ). Yet, a characteristic shared by most VBHC programs is the multifaceted approach that, on top of clinical outcomes, provides a prominent place to patient-reported quality and performance indicators.…”
Section: Introductionmentioning
confidence: 99%
“…Defining value and translating it into service delivery is not straightforward. Various stakeholders such as clients, managers and practitioners may have differing perceptions of what value is in occupational therapy services (Porter, 2010; Schapira et al, 2020). For example, some studies have observed that while clients valued participation-based goals, occupational therapists tended to set impairment- or activity-based goals that were achievable, measurable, and in line with organisational expectations and resource constraints (Leach et al, 2010; Rosewilliam et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Healthcare systems are gradually transitioning to "value-based healthcare" (VBHC) (Porter and Teisberg, 2006), with the goal of increasing care quality and performance, as well as equitable, sustainable, and transparent resource use (Hurst et al 2022). So far, there is no generally agreed-upon definition of VBHC (Schapira et al, 2020). However, a feature shared by most VBHC programs is a multimodal strategy that, in addition to clinical results, prioritizes patient-reported quality and performance measures.…”
Section: Introductionmentioning
confidence: 99%
“…Employee well-being should be included in the imperatives of healthcare organizations, according to the early proponents of VBHC, because healthcare professionals play an important role in VBHC (Porter and Teisberg, 2006). This correlates with the quadruple goal of (Porter and Teisberg, 2006) increasing patient health outcomes, (EXPH, 2019) improving patient experience, (Hurst et al, 2022) improving healthcare professional experience, and (Schapira et al, 2020) decreasing cost (Bodenheimer and Sinsky, 2014). In comparison to normal care approaches, VBHC may have an impact on professionals' work by introducing new or shifting emphasis toward value-promoting care activities and team-based care (Bohmer, 2011).…”
Section: Introductionmentioning
confidence: 99%